Hubungan Usia dan Aktivitas dengan Kenaikan Berat Badan Akseptor KB Suntik 3 Bulan Di TPMB Andrini Desa Selok Awar-Awar Kecamatan Pasirian - Agustin, Andrini Dwi; Rohmatin, Homsiatur; Farianingsih, Farianingsih (NHM PRESS, 2023)
Family planning is an action that helps married couples to avoid unwanted births, regulate birth spacing, and determine the number of children in the family by using hormonal or non-hormonal contraceptive methods. Combined contraceptives are available in pills and injections. While progestin contraceptives are found in injectable pills and implants. All types of contraception have advantages and disadvantages. The main drawbacks of injectable contraceptives are menstrual disorders, namely spotting, amenorrhea and menorrhagia, delayed return of fertility after discontinuation of use and weight gain. The effect of weight gain is because progestin stimulates the appetite control center in the hypothalamus which causes the hormone progesterone to facilitate the conversion of carbohydrates and sugar into fat, so that fat under the skin increases. In addition, factors that can trigger weight gain are age, activity patterns, nutritional patterns, psychological factors, and body metabolism. The purpose of this study was to determine the relationship between age and activity with weight gain of 3-month injection family planning acceptors. This study uses an analytic observational research design with a Cohort approach. The population in this study is the number of 3 month injection family planning acceptors who visited TPMB as many as 50 acceptors and the number of samples used was 30 acceptors with quota sampling technique, and statistical tests using Spearman rank correlation. The results showed that respondents aged 20-35 years who experienced weight gain were 12 respondents with the results of statistical tests with Spearman rank obtained p-value = 0.782 > 0.05 and respondents with light activities who experienced weight gain were 14 respondents with the results of statistical tests with spearman rank obtained p-value = 0.488> 0.05. So it can be concluded that there is no relationship between age and activity with weight gain of 3-month injection family planning acceptors at TPMB Andrini, Selok Awar-awar Village, Pasirian District, Lumajang Regency. Suggestions for acceptors are to really understand how big the side effects of using 3-month injectable contraceptives are.